2007
DOI: 10.1590/s1415-790x2007000200004
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização do consumo de maconha entre escolares do ensino médio de São José do Rio Preto, SP, Brasil, 2003

Abstract: OBJETIVO: Caracterizar o consumo de maconha entre escolares do ensino médio do município de São José do Rio Preto - SP. MÉTODO: Utilizou-se um estudo de corte transversal em escolas públicas do ensino médio com uma amostragem de conglomerados. Foram aplicados 1.041 questionários autopreenchíveis de maneira coletiva nas classes, mantidos sem identificação. As variáveis selecionadas foram cruzadas e para a associação foi realizado o teste do qui-quadrado com nível de significância de 5%. RESULTADOS: As prevalênc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
2
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
1
2
0
2
Order By: Relevance
“…Other available studies found similar results to ours for variables such as gender, age, skin color self-reported and marital status among secondary education students interviewed in the study (2,11) . Regarding family income, there was disagreement between the results for public and private schools, showing that the students of public schools belong to different economic strata.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Other available studies found similar results to ours for variables such as gender, age, skin color self-reported and marital status among secondary education students interviewed in the study (2,11) . Regarding family income, there was disagreement between the results for public and private schools, showing that the students of public schools belong to different economic strata.…”
Section: Discussionsupporting
confidence: 89%
“…Its use can be considered the initial step for the consumption of other more toxic illicit drugs. Pointing to the need for prevention campaigns against its use, because in the study conducted in São José do Rio Preto (11) it was found that among the consumption of other illicit and licit drugs, it is the most common among those who have tried marijuana. Therefore, the use of this substance can strengthen the idea of progression as the use of other licit and illicit drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Marijuana and inhalants were the most prevalent illicit PAS in the analyzed studies. Marijuana use is associated with many variables, including socioeconomic status and culture of each location (25) , which is often considered as a PAS without major consequences to the individual (26) . The high prevalence of inhalants use is usually associated with young people with poor socioeconomic situation, in which there is easier this access to this substance (14) .…”
Section: Discussionmentioning
confidence: 99%
“…O estudo apresenta limitações quanto à Tabela 4 -Com quem os escolares do ensino médio público aprenderam sobre drogas e quem escolheriam para conversar sobre drogas. SJRP, SP, N=1035* * Qui-quadrado / Chi-square ** Inclui as opções "Muito bem informado" e "Bem informado" / Includes options "Very well informed" and "well informed" *** Inclui as opções "Informado", "Razoavelmente informado" e "Pouco informado" / Includes options "Informed", "Reazonably informed" and "Litte informed" + Os totais não coincidem devido à falta de informação sobre algumas variáveis / A família tem influência na experimentação com drogas, com um bom relacionamento familiar servindo de proteção ao uso e também de auxílio na recuperação de usuários 5,11,13,[19][20][21] . Na entrevista com 30 usuários e 32 jovens que nunca utilizaram drogas, Sanchez et al (2005) identificaram maior influência da mãe na prevenção da experiência com drogas, e melhores relações com ela do que com o pai 11 .…”
Section: Discussionunclassified
“…Assim, podemos supor que os 39,9% de escolares cujos pais não vivem juntos ou com bom relacionamento estão mais suscetíveis ao uso de drogas (Tabela 1). A correlação entre o consumo de drogas e o relacionamento familiar nessa população identificou maior uso de maconha entre aqueles que não referiram os pais viverem juntos e com bom relacionamento 21 , e maior consumo desta e outras drogas entre aqueles que referiram uma relação com os pais diferente de ótima ou boa 20,21 .…”
Section: Discussionunclassified